1987
DOI: 10.1177/07399863870092004
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Alcohol Use: Drinking Patterns and Problems among Anglo and Mexican American Male Drinkers

Abstract: Data are presented on drinking patterns and alcohol-related problems among 164 Anglo and 149 Mexican American male regular drinkers. The paper examines the role of acculturation with regard to alcohol use by categorizing Mexican American respondents into three acculturation groups using a multi-item measure developed for this study. Data from a random sample of males drinking at least 2-3 times a month, aged 20-50, showed that, even after socio-demographic controls, Mexican Americans were less frequent, but hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
72
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 6 publications
2
72
1
Order By: Relevance
“…In the acculturation literature, Mexican Americans who reported more acculturation tended to endorse more reasons for drinking related to social aspects, whereas less acculturated individuals reported drinking for more coping reasons (Caetano and Medina Mora, 1988;Neff et al, 1987). Similarly, it is possible that study-abroad students with greater positive sojourner adjustment would be more likely to endorse social reasons for drinking, whereas those with more negative sojourner adjustment would be more likely to drink to cope with feeling detached, anxious, or depressed in the foreign environment.…”
Section: Drinking Motivesmentioning
confidence: 99%
“…In the acculturation literature, Mexican Americans who reported more acculturation tended to endorse more reasons for drinking related to social aspects, whereas less acculturated individuals reported drinking for more coping reasons (Caetano and Medina Mora, 1988;Neff et al, 1987). Similarly, it is possible that study-abroad students with greater positive sojourner adjustment would be more likely to endorse social reasons for drinking, whereas those with more negative sojourner adjustment would be more likely to drink to cope with feeling detached, anxious, or depressed in the foreign environment.…”
Section: Drinking Motivesmentioning
confidence: 99%
“…These studies often show conflicting results (Black et al, 1993;Corbett et al, 1991;Caetano, 1987;Caetano, 1988;Nielsen, 2001;Randolph et al, 1998). For example, acculturation may lead to abstention or more frequent drinking depending upon the region in which the immigrant resides (Caetano, 1989); alcohol use increases with increasing acculturation among females (Borges et al, 2006;Caetano et al, 1988;Neff and Hoppe, 1992;Vega and Amaro, 1994;Zemore, 2005) but less so or not at all among males (Borges et al, 2006;Marin, 1996;Marin and Marin, 1997;Marin and Posner, 1995;Neff and Hoppe, 1992;Zemore, 2005); alcohol consumption decreases among the more highly acculturated (Markides et al, 1990;Murguia et al, 1998;Neff et al, 1987;Neff and Hoppe, 1992); and drinking context varies (Gilbert, 1985;Gilbert, 1988;Gilbert and Cervantes, 1986). Assumptions about the relationship between acculturation and alcohol use, together with methodological limitations in the use of alcohol outcomes, control, and moderating variables in studies, have been used to explain the inconsistent results (Gutmann, 1999;Zemore, 2005).…”
Section: Alcohol and Drug Use In The Us Hispanic Populationmentioning
confidence: 99%
“…Among Latina women, greater acculturation is associated with higher odds of being a drinker and higher levels of alcohol consumption (Caetano, 1987;Caetano and Medina-Mora, 1988;Marks et al, 1990;Zemore, 2005). Among Latino men, the nature of the relationship between acculturation and drinking is less clear: Studies have suggested positive (Cherpitel, 1999;Marks et al, 1990), negative (Hines and Caetano, 1998;Markides et al, 1988;Neff et al, 1987), and curvilinear (Caetano, 1987;Caetano and Clark, 2003;Polednak, 1997) relationships between acculturation and other drinking outcomes, as well as null results (Alaniz et al, 1999;Caetano and MedinaMora, 1988;Ye et al, 2005;Zemore, 2005; for a review, see Zemore, 2007).…”
mentioning
confidence: 99%
“…That is, for those with high income, higher acculturation would be related to higher odds of drinking, but for those with low income, acculturation would not be related to drinker status. Based on studies examining acculturation's effects on drinking among drinkers only (Neff et al, 1987), we expected that the drinking men in our sample who were at high levels of acculturation would drink less often, consume less alcohol, engage in less heavy drinking, and have lower odds of dependence than their peers at low or medium levels of acculturation. We also tested exploratory hypotheses that income would moderate the associations between acculturation and the behavior of drinkers based on the assumption that income is associated with normative infl uences that may be related to drinking outcomes among drinkers.…”
mentioning
confidence: 99%